2009
DOI: 10.1055/s-0029-1214758
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lymph node metastasis in histologically poorly differentiated type early gastric cancer

Abstract: A histologically poorly differentiated type mucosal gastric cancer measuring less than 20 mm and without LVI may be a candidate for endoscopic resection. This result should be confirmed in a larger study with many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 21 publications
8
39
0
1
Order By: Relevance
“…Similar findings were observed in our previous work, a Korean study performed by another group, and two Japanese studies [9,10,14,16]. These observations suggest that in undifferentiated EGC, the risk of lymph node metastasis depends more on submucosal invasion and lymphovascular invasion than it does on histologic subtype, such as poorly differentiated or signet ring cell type.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were observed in our previous work, a Korean study performed by another group, and two Japanese studies [9,10,14,16]. These observations suggest that in undifferentiated EGC, the risk of lymph node metastasis depends more on submucosal invasion and lymphovascular invasion than it does on histologic subtype, such as poorly differentiated or signet ring cell type.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have reported tumor length cutoff values for only one histologic subtype or for the united undifferentiated type. Kunisaki et al [16] proposed a cutoff length of 20 mm in poorly differentiated EGC with mucosal invasion but without lymphovascular invasion, and Park et al [21] and Li et al [22] proposed cutoffs of 15 and 20 mm, respectively, in poorly differentiated EGC. For signet ring cell EGC, Ha et al [14] and Park et al [15] proposed 20 and 25 mm as cutoff lengths, respectively.…”
Section: \00001mentioning
confidence: 99%
“…There have been several reports showing indications for endoscopic treatment of EGC of the undifferentiated type in view of a minimal risk of lymph node metastasis, because most EGCs are cured by surgical gastrectomy with lymph node resection [7,8,9,10,11,12,13,14,15]. Gotoda et al [16] showed there were no lymph node metastases in the intramucosal lesions <20 mm in diameter and no ulceration findings in the study of 2,341 cases of undifferentiated carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pathological analyses of resected specimens have revealed that lymph node involvement is found in less than 20% of patients, and metastasis to the second tier lymph nodes is especially rare in patients with early gastric cancer in Japan (1)(2)(3)(4). Recently, sub-total or total gastrectomy with a reduced lymphadenectomy, depending on the clinical and surgical findings, has been recommended in the guidelines for treating gastric cancer edited by the Japanese Gastric Cancer Association (JGCA guidelines) (5).…”
Section: Introductionmentioning
confidence: 99%